2020
DOI: 10.7189/jogh.10.0201302
|View full text |Cite
|
Sign up to set email alerts
|

Social mobilization campaign to tackle immunization hesitancy in Sargodha and Khushab districts of Pakistan

Abstract: Background Immunization hesitancy is a delay in acceptance or refusal of vaccines despite availability of vaccination services. If people are not engaged appropriately via communication and social mobilization, doubts about the trade-offs between the benefits and potential side effects persist. The objective of this study was to explore strategies for improved social mobilization to reduce immunization hesitancy.Methods Mix of quantitative and qualitative approaches was applied to collect data from a diverse g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
1
14
0
1
Order By: Relevance
“…These positive findings on the knowledge about, and use of, ORS during diarrheal episodes might be due to various health education programs implemented by the Government of Pakistan. The Lady Health Worker (LHW) program and education via mass media have enabled caregivers to identify and manage common preventable illnesses, including diarrhea (Malik et al, 2020 ; Ronis & Nishtar, 2007 ). However, several studies reported that mothers and other caregivers in Pakistan still treat diarrhea in children with home remedies or self-prescribed medication, including antibiotics, and only one third of caregivers manage pediatric diarrhea using ORS (Aftab et al, 2018 ; Khan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These positive findings on the knowledge about, and use of, ORS during diarrheal episodes might be due to various health education programs implemented by the Government of Pakistan. The Lady Health Worker (LHW) program and education via mass media have enabled caregivers to identify and manage common preventable illnesses, including diarrhea (Malik et al, 2020 ; Ronis & Nishtar, 2007 ). However, several studies reported that mothers and other caregivers in Pakistan still treat diarrhea in children with home remedies or self-prescribed medication, including antibiotics, and only one third of caregivers manage pediatric diarrhea using ORS (Aftab et al, 2018 ; Khan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to dispel the misinformation that leads to decline in vaccination intent [32], there is need for the development of an effective communication strategy to create trust in the communities, raise awareness, and reveal myths regarding safety and efficacy of vaccines through consistent and evidence-based messages [33]. There is a need to take up vigorous awareness campaigns, telephonic messages, and pamphlets which describe the safety of the vaccine and the active engagement of NGOs [34] and community leaders/champions/employers and community associations [35]. This social mobilization should be utilized to disseminate correct and timely information over social media [36], newspapers, advertisement campaigns, and billboards to increase awareness.…”
Section: The Following Are Key Recommendationsmentioning
confidence: 99%
“…The objective was to affirm the commitment of the Government in the provision of vaccines and to align the national standards goals and messages toward vaccination. In this campaign, local religious influencers were involved through announcements in Mosque about immunization sessions and through the mentioning of immunization significance during periodic religious sermons (19). A preventive strategy to reduce the incidence of cervical cancer among immunized women in Malaysia consisted in the providing of HPV information followed by a free vaccination.…”
mentioning
confidence: 99%